The course and outcomes of monochorial monoamniotic twin pregnancy - S.A. Kalashnikov; A.G. Konoplyannikov; K.Yu. Voskoboeva; L.R. Semenova; I.S. Kulakova (LCC «Medicine-Inform», 2023)
S.A. Kalashnikov1, A.G. Konoplyannikov1, K.Yu. Voskoboeva1, L.R. Semenova1, I.S. Kulakova2 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2Bashkir State Medical University, Ufa, Russian Federation Aim: to evaluate the course and outcomes of monochorial monoamniotic (MCMA) twin pregnancy. Patients and Methods: this prospective study included 34 patients (a mean age 31.8±4.3 years) with MCMA twins for assessing the course of pregnancy and perinatal outcomes. The authors evaluated such criteria as the timing of delivery and the prenatal management of MCMA-twin pregnancy, as well as the perinatal outcomes and mortality. Monitoring of the pregnant women with umbilical cord entanglement was started at 16 weeks of gestation and included ultrasound examination every two weeks and after 26-28 weeks of gestation - two or three times a week coupled with cardiotocography for fetal assessment. Results: the study demonstrated a high prevalence of cervical insufficiency which was found in 10 (29.4%) MCMA twin pregnancies at 18 to 28 weeks of gestation. The diagnosis of umbilical cord entanglement was established in 16 (47.1%) patients, twin-twin transfusion syndrome (TTTS) - in 2 (5.9%) patients, and twin anemia-polycythemia syndrome (TAPS) - in 1 (2.9%) patient. The reported antenatal losses were 6 of 68 (8.8%) of fetuses. There were 7 perinatal losses of 68 MCMA-twin pregnancies (10.3%). The antenatal and perinatal losses in MCMA twins were caused by the following specific complications: TTTS, cord entanglement and hypoxia due to the selective intrauterine growth restriction (sIUGR). A preterm operative delivery was used in 29 (85.2%) patients with MCMA twins. Five (14.7%) patients did not have complications and it was possible to prolong the pregnancy to 36 weeks. Caesarean sections were carried out almost for all the pregnant women (33 (97.1%)). Conclusion: the antenatal and perinatal losses in MCMA twins are caused by the specific complications. These findings prove that patients with complicated MCMA twin pregnancies need to have a careful monitoring in Level III perinatal centers. Planned caesarean sections are recommended for all MCMA twin pregnancies. If complications are detected, a preterm operative delivery closer to week 35 of gestation will enable to increase the fetal survival rates and thus to improve the perinatal outcomes. Uncomplicated MCMA twin pregnancies can be prolonged to week 36 for improving the condition of newborn babies at the time of delivery. Keywords: multifetal pregnancy, monochorial monoamniotic twin pregnancy, umbilical cord entanglement, neonatal outcome, twin-twin transfusion syndrome, selective intrauterine growth restriction, twin anemia-polycythemia syndrome. For citation: Kalashnikov S.A., Konoplyannikov A.G., Voskoboeva K.Yu. et al. The course and outcomes of monochorial monoamniotic twin pregnancy. Russian Journal of Woman and Child Health. 2023;6(1):6-12 (in Russ.). DOI: 10.32364/2618-8430-2023-6-1-6-12.